Relationship between Health Status and Organic Solvent Level in Handicraft Workers in Chiangmai Province - ขันติพงศ์, เจียรนัย; ด่านไพบูลย์, อนงค์ศิลป์; หลิวเสรี, วิทยา; ชัยสุวรรณ, ชาญณรงค์; คชาอนันต์, ศุภกิจ; สิงห์แก้ว, จรัส; นามบุญมี, โกวิทย์; ท้วมแสง, สมเกียรติ์ (Disease Control Journal, 2012)
The aim of this study was to detect the blood level of organic solvents (Acetone, Isopropaanol, Toluene, Trichloroethylene and Hexane) in handicraft workers,Chiangmai province. In addition, the relationbetween blood solvents level and workers' health was determined. The subject categorized in exposed (n=150) and non-exposed group (n = 150) based on their self report questionaire. The exposed group was usually contact to organic solvent, while the non-exposure group was the same company worker but their job was not directly exposed or contact to organic solvent. Blood samples were collected at the end of morning shift.Organic solvents (parent compound) were detected by using Headspace-Gas Chromatography with Flame ionization detector (HS-GC-FID). Complete blood count, liver function test and kidney function test were also examined to determine a health status of workers. The result showed that the level of Trichloroethylene in exposed group was higher than non-exposed group (p<0.05). The relationship were shown on trichloroethylene level among number blood urea nitrogen (r = 0.67; p=0.038). In conclusion, the worker who exposed organic solvent during working found the trichloroethylene in blood and related to liver function so the data represent the deleterious effect of trichloroethylene exposure. The management of industry, working process and health surveillance of working who exposed to trichloroethylene is the most important especially informal workers which will be studied.